Linking HRM practices and institutional setting to collective turnover: An empirical exploration - Dirk van Dierendonck; Arthur Lankester; Maria Zmyslona; Hans Rothweiler (Administrative Sciences, 2016)
The present study addresses the relationship between human resources management (HRM) practices and employee turnover by taking into account the influence of socioeconomic environment. Data was collected at company level with an international sample of 830 companies from 12 countries (Netherlands, Belgium, United Kingdom, Brazil, Switzerland, China, France, Italy, Poland, Germany, South Africa, and Spain). A division into four bundles of human resources (HR) practices is introduced: remunerative, communication, developmental, and well-being practices. The influence of the socioeconomic environment was factored in by including the institutional setting in terms of the level of coordination as a country-level variable. The results showed that collective turnover is related to both a country's institutional determinants and to company HR practices. Remunerative HR practices may have a negative influence in terms of enhancing turnover, particularly within countries high in coordination. HR well-being practices are the most beneficial practices in terms of reducing employee turnover. Our study adds to our knowledge on the relation between HR practices and turnover from an international perspective. It complements the empirical knowledge on the effectiveness of HRM practices in a cross-national setting and supports the notion that the institutional context should be given more attention when studying HR effectiveness.
Keywords: 350; HRM practices; collective turnover; institutional context